Atomic origin of room-temperature two-dimensional itinerant ferromagnetism in an oxide-monolayer heterostructure. (September 2021) - Liu, Heng-Jui; Ye, Mao; Yang, Chao-Yao; Fang, Yue-Wen; Chin, Yi-Ying; Chen, Chun-Ying; Hung, Ruei Tze; Zhu, Yuanmin; He, Liang-Ching; Huang, Min-Yuan; Chen, Lang; Gu, Meng; et al.
Highlights: Successful demonstration of the oxide-monolayer-based superlattice with room-temperature 2D itinerant ferromagnetism. The presence of room-temperature 2D ferromagnetism and anomalous hall effect offers the opportunity to develop the all-oxide-based spintronic devices. A new finding of charge-transfer-induced antiferromagnetism at interfaces instead of conventional defect mechanism dominates this room-temperature 2D ferromagnetism. Abstract: Materials with room-temperature two-dimensional itinerant ferromagnetism enable ultracompact device density and quantum computing in next-generation nano-spintronics. Among numerous candidates, perovskite-based heterostructures have offered an excellent platform to manipulate spin-orbital-charge coupling, unveiling a series of emergent spin-dependent phenomena. In this work, we have fulfilled a robust room-temperature soft ferromagnetism together with a metallic characteristic based on a high quality SrRuO3 -monolayer-based superlattice. Further examination on this short-range ferromagnetism has been carried out by synchrotron-related spectroscopy, where charge-transfer-induced antiferromagnetic coupling between partial Ru and Ti ions have been found. Although such local antiferromagnetic coupling would break long range ferromagnetic order, it simultaneously stabilize the localized intralayer ferromagnetic order in the SrRuO3 monolayers, which is confirmed by theoretical calculations. Our study not only represents a methodological advance of achieving fantastic magnetic properties in functional oxide monolayer, but is promising to unlock new opportunities for oxide-based spintronic devices toward room-temperature applications. Graphical abstract: Image, graphical abstract